THEORIES OF INTERNATIONAL TRADE: EMERGING KNOWLEDGE - Maxwell Nwinye (Scholars Digest Publishing, 2025)
Trade is a business relationship that involves exchanging goods and services between two people or entities. International trade entails the concept of exchanging skills, technology, weapons, goods and services across national frontiers or between two countries. The factors that enhance trade are complex, and economists throughout the centuries have attempted to interpret the inclinations and factors through the evolution of trade theories. No country likes to trade with its enemy but countries engage in international business to promote world peace and exploitation of new technology. This study examined roles of theories of international trade. The study revealed that understanding the theories of international trade may help consumers or countries to penetrate foreign markers. The concept of theories of international trade especially technology gap theory and absolute advantage theory assist countries that do not produce a specific product to benefit from it through import.
Keywords: Mercantilism theory, absolute advantage theory, comparative advantage theory.